Atomic‐Scale Engineering: Anion Constructor for Atomic‐Scale Engineering of Antiperovskite Crystals for Electrochemical Reactions (Adv. Funct. Mater. 16/2021). (15th April 2021) - Lee, Sehyun; Jung, Jae Young; Jang, Injoon; Choi, Daeil; Lee, Myeong Jae; Lee, Dong Wook; Jang, Jue‐Hyuk; Lee, Jeong Hee; Jin, Haneul; Im, Kyungmin; Lee, Eungjun; Kim, Seung‐hoon; et al.
Abstract : In article number 2009241, Docheon Ahn, Pil Kim, Sung Jong Yoo, and co‐workers synthesize monolithic antiperovskite crystals through atomic‐scale engineering. The nitride PdNi alloy achieves excellent catalytic activity and durability under acidic media, resulting from the synergistic effect of nitride and intermetallic structures. This strategy will pave the way for overcoming the catalytic performance of potential materials.